2019
DOI: 10.2116/analsci.19p288
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Lysozyme in Viscous Raw Hen Egg White Binding to Sodium Dodecyl Sulfonate by Reactive Wooden-tip Electrospray Ionization Mass Spectrometry

Abstract: Direct characterization of native protein binding to ligands in raw biological samples is a challenging task, because the ligand solution might induce proteins to aggregation, flocculation and denaturation. In this work, we developed a reactive wooden-tip electrospray ionization mass spectrometry (ESI-MS) for formation and characterization of protein-ligand complexes upon rapid mixing in electrospray droplets. Raw viscous hen egg white (HEW) was directly loaded onto a wooden tip to induce spray ionization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Particularly, free heme at m/z 616.18 was detected; the heme detection confirmed that Hb is totally denatured under the organic solvent. Low-background-noise (Figure 1c) solvent is generated a from blank wooden material that is similar to a previous work using wooden-tip ESI [32][33][34].…”
Section: Direct Analysis Of Whole Blood Samplesmentioning
confidence: 84%
See 1 more Smart Citation
“…Particularly, free heme at m/z 616.18 was detected; the heme detection confirmed that Hb is totally denatured under the organic solvent. Low-background-noise (Figure 1c) solvent is generated a from blank wooden material that is similar to a previous work using wooden-tip ESI [32][33][34].…”
Section: Direct Analysis Of Whole Blood Samplesmentioning
confidence: 84%
“…It is reported that different protein structures can be recognized by ambient MS [31]. In previous studies [32,33], WT-ESI-MS has been successfully used for protein analysis. Furthermore, the mobility of proteins in wooden tips could be characterized under ESI conditions [34].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2(F), the wooden tip was directly mounted on a nanoESI device of an Orbitrap mass spectrometer (Q‐Exactive, Thermo Fisher Scientific, Bremen, Germany) as described previously 23,24 . Briefly, the distance between the wooden tip‐end and MS inlet was ca.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, native mass spectrometry has been used to characterise allergens and their interactions, with one study using novel wooden tips to analyse egg white. 41,42 In this study we apply an adapted version of this methodology to the analysis of protein rich natural products. We deliberately chose examples that are sources of commercially available "standard" proteins, as well as widely consumed food substances.…”
Section: Introductionmentioning
confidence: 99%